HANDLOOM AND CONSTRUCTION OF IDENTITY: A STUDY AMONG THE BODO WOMEN WEAVERS OF ASSAM - Basumatary, Rishma; Khawzawl, Teresa L. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The practice of handloom weaving holds significant historical and cultural importance for the Bodo community, serving as an integral aspect of their socio-economic fabric for countless generations. In addition to engaging in agricultural activities, the Bodo community, along with the wider rural and semi-urban population of India, have traditionally pursued handloom weaving as a secondary occupation. The significance of handloom textile and weaving in the lives of the Bodo weavers can be understood via two distinct dimensions. Firstly, at the local level, it serves as a manifestation of local wisdom and tradition deeply ingrained into their cultural practices. Secondly, at the national level, it acts as a tangible representation of the community's distinctive identity. This article attempts to comprehend the importance of weaving within the Bodo community, specifically among women weavers, and examines how their involvement in the handloom sector contributes to the development of cultural identity. Nevertheless, it is crucial to comprehend the viewpoint of the weavers in their commitment to the preservation of the weaving practice, as they assume the role of custodians and guardians of this longstanding heritage.